Copyright Violation in Works of Art Using the Form of Non-Fungible Tokens (NFT) in the Era of Digitalization - Dimas Yoga; Tri Susilowati; Mohamad Tohari (PT. Publikasiku Academic Solution, 2024)
Intellectual Property Rights (IPR) are exclusive rights granted by the state to individuals or groups to safeguard their intellectual works. Such works may include inventions, works of art, writings, designs, and trademarks, among others. In Indonesia, IPR is regulated by several laws, including the Patents Law (Law Number 13 of 2016), Copyright Law (Law Number 28 of 2014), and Marks and Geographical Indications Law (Law Number 20 of 2016), among others. These rights encompass copyrights, patents, trademarks, industrial designs, trade secrets, and other related rights. The purpose of IPR protection is to encourage innovation and creativity by providing legal protection for the fruits of intellectual labor, thereby enabling individuals and organizations to reap the benefits of their efforts. Businesses and individuals must understand IPR laws and regulations, as they affect the ownership, licensing, and transfer of intellectual property assets. Violation of two-dimensional works of art and NFTs is a form of crime in digital economic activities, in this case, the government must intervene to overcome this crime. The issue at hand is a direct result of insufficient legal regulations governing the digital realm. Cybercrime, which encompasses a multitude of illicit or perilous activities that take place in the virtual world or through the utilization of computer and internet technology, encompasses copyright infringement. This form of wrongdoing entails the contravention of intellectual property rights, such as the unlawful distribution of music or films, software piracy, or the unauthorized use of trademarks. Legal protection pertains to regulations that are concerned with digital works of art.